Polymorphic inverted repeats near coding genes impact chromatin topology and phenotypic traits in Arabidopsis thaliana - Arce, Agustín Lucas (2023)
Transposons are mobile elements that are commonly silenced to protect eukaryotic genome integrity. In plants, transposable element (TE)-derived inverted repeats (IRs) are commonly found near genes, where they affect host gene expression. However, the molecular mechanisms of such regulation are unclear in most cases. Expression of these IRs is associated with production of 24-nt small RNAs, methylation of the IRs, and drastic changes in local 3D chromatin organization. Notably, many of these IRs differ between Arabidopsis thaliana accessions, causing variation in short-range chromatin interactions and gene expression. CRISPR-Cas9-mediated disruption of two IRs leads to a switch in genome topology and gene expression with phenotypic consequences. Our data show that insertion of an IR near a gene provides an anchor point for chromatin interactions that profoundly impact the activity of neighboring loci. This turns IRs into powerful evolutionary agents that can contribute to rapid adaptation.